Implementing Learning Management Systems To Support Digital Transformation In Education: A Case Study Of Business English Learning - Rizki Hardiyanti; Friscila Purba; Laras Afifah; Noni Noerkaisar (CV Putra Publisher, 2026)
The rapid advancement of digital technology has increased the need for digital transformation in higher education. This study examines the implementation of Learning Management Systems (LMS) in supporting educational digital transformation and explores their role in enhancing innovative learning practices in a Business English course. A descriptive qualitative case study approach was employed. Data were collected through interviews, classroom observations, and document analysis involving lecturers and students who had used the LMS for at least one semester. The findings reveal that LMS implementation improves learning accessibility, promotes interactive and student-centered learning, and supports flexible technology-based instruction. In the context of Business English, the LMS facilitates the use of digital modules, discussion forums, and task-based assessments aligned with workplace communication skills. However, challenges related to digital literacy, infrastructure readiness, and pedagogical adaptation remain. This study concludes that effective LMS implementation contributes to digital transformation in education when supported by institutional policies, continuous training, and pedagogical innovation. These findings offer practical implications for higher education institutions seeking to optimize LMS utilization as part of their digital transformation strategies.